Kinerja Dan Efisiensi Sektor Publik Di Kabuapen/Kota Provinsi Nusa Tenggara Barat - Wahyunadi Wahyunadi (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2019)
This study aims to measure regional financial management related to theachievement of development targets through measuring performance and efficiency of the public sector. The method of analysis in this study is to measure the performance of the public sector and the efficiency of the public sector by using the method of Public sector performance (PSP) and Public sector efficiency (PSE). The results of the calculation of public sector performance (PSP) and public sector efficiency (PSE) in districtsin West Nusa Tenggara show that using social indicators namely health and education while the standard indicators of musgravian are distribution, stabilization and economic performance. District which has the highest total indicator value of Public Sector Performance (PSP) is Mataram City followed by West Lombok Regency and West Sumbawa Regency. Districts that have the highest indicator of the total value of the Public Sector Efficiency (PSE) are Sumbawa Regency and Mataram City followed by North Lombok Regency. Whereas the District with the lowest total indicator of the Public Sector Efficiency (PSE) is Dompu Regency.